An autolysin ring associated with cell separation of Staphylococcus aureus. - Yamada, S (1996)
atl is a newly discovered autolysin gene in Staphylococcus aureus. The gene product, ATL, is a unique, bifunctional protein that has an amidase domain and a glucosaminidase domain. It undergoes proteolytic processing to generate two extracellular peptidoglycan hydrolases, a 59-kDa endo-beta-N-acetylglucosaminidase and a 62-kDa N-acetylmuramyl-L-alanine amidase. It has been suggested that these enzymes are involved in the separation of daughter cells after cell division. We recently demonstrated that atl gene products are cell associated (unpublished data). The cell surface localization of the atl gene products was investigated by immunoelectron microscopy using anti-62-kDa N-acetylmuramyl-L-alanine amidase or anti-51-kDa endo-beta-N-acetylglucosaminidase immunoglobulin G. Protein A-gold particles reacting with the antigen-antibody complex were found to form a ring structure on the cell surface at the septal region for the next cell division site. Electron microscopic examination of an ultrathin section of the preembedded sample revealed preferential distribution of the gold particles at the presumptive sites for cell separation where the new septa had not been completed. The distribution of the gold particles on the surface of protoplast cells and the association of the gold particles with fibrous materials extending from the cells suggested that some atl gene products were associated with a cellular component extending from the cell membrane, such as lipoteichoic acid. The formation of a ring structure of atl gene products may be required for efficient partitioning of daughter cells after cell division.